2002
DOI: 10.1074/jbc.m107124200
|View full text |Cite
|
Sign up to set email alerts
|

Brn-4 Transcription Factor Expression Targeted to the Early Developing Mouse Pancreas Induces Ectopic Glucagon Gene Expression in Insulin-producing β Cells

Abstract: The endocrine pancreas is comprised of ␤ and ␣ cells producing the glucostatic hormones insulin and glucagon, respectively, and arises during development by the differentiation of stem/progenitor cells in the foregut programmed by the ␤ cell lineage-specific homeodomain protein Idx-1. Brain-4 (Brn-4) is expressed in the pancreatic anlaga of the mouse foregut at e10 in the ␣ cells and transactivates glucagon gene expression. We expressed Brn-4 in pancreatic precursors or ␤ cell lineage in transgenic mice by pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 30 publications
0
32
1
Order By: Relevance
“…Among those enriched in the ␣ cell is brain 4, which is specifically expressed in islet progenitors and differentiating, as well as adult, ␣ cells. It functions as an essential transactivator in glucagon gene expression and possibly as a dominant regulator of ␣ cell lineages (54). This is the HD protein showing the greatest differential in expression, and our data highlight its essential contribution to the ␣ cell's unique development and functional profile.…”
Section: Discussionmentioning
confidence: 85%
“…Among those enriched in the ␣ cell is brain 4, which is specifically expressed in islet progenitors and differentiating, as well as adult, ␣ cells. It functions as an essential transactivator in glucagon gene expression and possibly as a dominant regulator of ␣ cell lineages (54). This is the HD protein showing the greatest differential in expression, and our data highlight its essential contribution to the ␣ cell's unique development and functional profile.…”
Section: Discussionmentioning
confidence: 85%
“…Temporal and spatial expression of HD proteins affecting the commitment of cell lineage in pancreatic islets has been documented. For example, Hussain et al (2002) reported that ectopic misexpression of the POU HD protein Brn-4 by Pdx-1 promoter in transgenic mice resulted in ectopic expression of the glu gene in insulin-expressing pancreatic cells, while misexpressing Brn-4 by rat insulin II promoter did not.…”
Section: Discussionmentioning
confidence: 99%
“…Although transgene expression in pancreatic islets of rodents has been achieved by microinjection of fertilized embryos (24)(25)(26)(27)(28)(29)(30), safe and efficient in vivo targeting of genes to pancreatic islets has been an elusive goal. This paper describes a method for efficient gene delivery to the pancreatic islets, with detection of transgene-encoded proteins (luciferase, human insulin and Cpeptide, hexokinase I) for up to 3 weeks after transfection.…”
Section: Discussionmentioning
confidence: 99%